The crystal structure of tris(6-methylpyridin-2-yl)phosphine oxide, C18H18N3OP - Wu Gui-Ling (Zeitschrift für Kristallographie - New Crystal Structures)
C18H18N3OP, monoclinic, P21/n (no. 14), a = 13.3987(17) Å, b = 8.7084(11) Å, c = 14.5063(18) Å, β = 95.849(2)° V = 1683.8(4) Å3, Z = 4, Rgt(F) = 0.0423, wRref(F2) = 0.1311, T = 296(2) K.